2011
DOI: 10.1021/jp2062496
|View full text |Cite
|
Sign up to set email alerts
|

Protein–Surfactant Interaction: Sodium Dodecyl Sulfate-Induced Unfolding of Ribonuclease A

Abstract: Protein-surfactant interaction is widely studied to understand stability and structural changes in proteins. In this Article, we have investigated SDS-induced unfolding of RNase A using absorbance, intrinsic fluorescence of the protein, anisotropy, TNS fluorescence, and near- and far-UV circular dichroism. Unfolding titration curves obtained from the absorbance and fluorescence changes were fitted into a five-state protein unfolding model by assuming formation of three intermediate states. Free energy changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…The FP spectroscopy was previously used to inspect: (i) the interactions of mild 14 and harsh 15 detergents with water-soluble proteins, (ii) the harsh detergent-induced unfolding 16 and resistance of soluble proteins to denaturation, 17 (iii) the detergent-mediated oligomerization of hydrophobic proteins into proteomicelles, 18 and (iv) the impact of detergent on conformational changes 14 and enzymatic activity 19 of soluble proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The FP spectroscopy was previously used to inspect: (i) the interactions of mild 14 and harsh 15 detergents with water-soluble proteins, (ii) the harsh detergent-induced unfolding 16 and resistance of soluble proteins to denaturation, 17 (iii) the detergent-mediated oligomerization of hydrophobic proteins into proteomicelles, 18 and (iv) the impact of detergent on conformational changes 14 and enzymatic activity 19 of soluble proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This assay relied on the use of fluorescence polarization (FP) spectroscopy. 1518 In the past, FP spectroscopy was employed for inspecting the PDC interactions with either mild 19 or harsh detergents 2022 and water-soluble proteins. In contrast to this work, prior sodium dodecyl sulfate (SDS)-protein interaction studies were focused on the mechanistic understanding of harsh detergent-induced protein unfolding 22 and resistance of proteins to denaturation 21 under diverse environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that lysozyme can easily form amyloid fibrils under different conditions, such as high temperatures and appropriate pH conditions [ 37 40 ]. Many amyloidogenic proteins interact with the surfaces of basement membranes; SDS has the potential to mimic this condition [ 29 , 41 45 ]. Furthermore, SDS surfactants mimic the bio-membrane environment and can provide anionic conditions through their anionic head groups [ 42 , 46 ].…”
Section: Introductionmentioning
confidence: 99%